AB0707 LTBI SCREENING IN SPONDYLOARTHRITIS PATIENTSPRIOR TO ANTI-TNF TREATMENT AND FOLLOW-UP IN AN ENDEMIC AREA. (June 2019) - Shimabuco, Andrea; Medeiros, Ana; Miossi, Renata; Bonfiglioli, Karina; Moraes, Julio; Gonçalves, Celio; Sampaio-Barros, Percival D.; Goldenstein-Schainberg, Claudia; Souza, Fernando; Prado, Leandro; Lopes, Michelle; Bonfa, Eloisa; et al.
Abstract : Background: Screening for latent tuberculosis infection (LTBI) remains a concern in endemic regions for anti-TNF eligible patients and recent researches have shown peculiarities between the inflammatory arthropathies such as different groups of spondyloarthritis (SpA). Objectives: To evaluate the long-term efficacy of LTBI screening and treatment in patients with ankylosing Spondylitis (AS) and Psoriatic arthritis (PsA) receiving TNF blockers in a single center. Methods: A total of 218 SpA patients (135 aS and 83 aPS) were screened for LTBI before receiving anti-TNF (infliximab, adalimumab, etanercept, certolizumab pegol and golimumab) treatment using the tuberculin skin test (TST), chest X-ray (CXR) and history of previous exposure to tuberculosis (TB). Patients were regularly followed every 2-3 months and asked about infectious symptoms or new exposure. TST was not repeated regularly. LTBI patients were treated with isoniazid (300 mg/day) for 6 months, according local guidelines. Results: One hundred and eight patients (49.5%) were treated with a single anti-TNF agent and the total duration of biological treatment was approximately six years (5.9 ± 4.0). InF and aDA were most often used among the 422 treatment cycles analyzed, representing 45% and 30% respectively. LTBI screening was positive in 82 patients (38%): 69 (84%) were TST-positive, 23(28%) had a history of TB exposure and 5(6%) had an abnormal CXR. As isolated variables TST positivity and previous exposure accounted for 58(71%) and 11 (13%) LTBI diagnosis. There were some distinct patterns between aPS and aS patients screening: despite aPS patients had more cases of previous TB than aS patients (6% vs 0.7%, P= 0.03), they had a lower frequency of LTBI (30% vs 42%, P = 0.04). Among LTBI patients, TST positivity was lower in SpA than aS patients (64% vs 93%, P = 0.002), even with more previous exposure (52% vs 18%, P = 0.02) and in patients with peripheral arthritis (27% vs 42%, P = 0.03). During follow-up, 11 patients developed active TB: 5 under aDA, 5 under inF and 1 under ETA treatment. Five cases (45%) were extrapulmonary: 3 pleural, 1 peritoneal and 1 spondylodiscitis. Four (36%) cases occurred in patients with a positive LTBI screening and 7 in patients without LTBI. There was no difference in drug survival according to type or class of anti-TNF, disease subgroups, duration or use of synthetic drugs and prednisone. Four (36.3%) cases occurred in the first year, median 5.3 (1.2-8.8) months after initiating anti-TNF exposure, 2 of them (50%) in patients with positive LTBI. Seven cases were probably due to re-exposure since occurred later, median 21.9 (14.2-42.8) months (5 in patients with negative LTBI screening). Six patients (54.5%) re-initiated treatment with ETA. Only the patient who developed pulmonary TB under ETA had a second TB infection after 18 months of therapy. Conclusion: Despite the adequate screening and treatment of LTBI, according to local guidelines, TB still occurs in spondyloarthritis patients under anti-TNF therapy, even in the first year of treatment. These data point to LTBI screening/treatment failure, maybe to due to anergy, mainly in PsA patients, with peripheral disease, low adherence or re-exposition in an endemic environment. The high frequency of extrapulmonary disease is also a diagnostic challenge. References: [1] Cantini F, Nannini C, Niccoli L, et al; SAFEBIO (Italian multidisciplinary task force for screening of tuberculosis before and during biologic therapy). Guidance for the management of patients with latent tuberculosis infection requiring biologic therapy in rheumatology and dermatology clinical practice. Autoimmun Rev. 2015Jun;14(6):503-9. Disclosure of interests: Andrea Shimabuco: None declared, ana Medeiros: None declared, Renata Miossi : None declared, Karina Bonfiglioli Speakers bureau: Has received speaking fees from Roche, Pfizer, Bristol-Myers Squibb, abbvie and Janssen., Julio Moraes: None declared, Celio Gonçalves: None declared, Percival D. Sampaio-Barros: None declared, Claudia Goldenstein-Schainberg: None declared, Fernando Souza: None declared, Leandro Prado: None declared, Michelle Lopes: None declared, Eloisa Bonfa: None declared, Carla Saad: None declared